Fire Safety of Historical Buildings Traditional Versus Innovative "Behavioural Design" Solutions by Using Wayfinding Systems - Bernardini, Gabriele (SpringerBriefs in Applied Sciences and Technology,, 2017)
This book applies a behavioral point of view to individuals' fire safety in historic buildings. It outlines theoretical and operative issues, based on recent studies and international guidelines. Firstly, critical issues for Building Heritage fire safety are widely discussed, by including the modelling of human factor and man-environment-fire interference in these architectural spaces. A significant part of the book includes a discussion on emergency modeling and simulation. A source code for representing the fire evacuation process (including man-evacuation facilities interactions) is offered to the reader. Methods for effectiveness assessment of risk-reducing solutions are provided and tested in a case-study. Being a structured approach to occupants-related problems during a fire in heritage buildings, it offers an innovative methodology and practical examples that researchers and designers can use as a guide when proposing and testing solutions. Evaluation indexes for effectiveness assessment (also useful for future guidelines or handbooks) are included. Readers are encouraged to understand these indexes within the proposed approach, so as to extend their applications and possibilities of how to introduce human behaviors-based solutions in other fields. Lastly, attention is focused on the proposal and evaluation of low-impact and not-invasive strategies, such as ones based on wayfinding elements. From this point of view, the pros and cons of wayfinding systems are discussed: these are important today, especially for fire-safety designers, because of the ongoing innovations in this field. .